322 High-Resolution Small Vessel Imaging With Rotational Angiography CT for Stereotactic Electroencephalographic Trajectory Planning. (1st August 2016) - Lang, Michael J.; Wu, Chengyuan; Jabbour, Pascal; Sharan, Ashwini Dayal
Abstract: INTRODUCTION: Vascular imaging is essential to safe planning of stereotactic trajectories. This is particularly true for Stereo electroencephalographic (EEG) trajectory planning, in which nonuniform trajectories are utilized to interrogate deep structures or optimize recordings for a particular hypothesis test. Rotational angiography with 3-dimensional computed tomographic (CT) reconstruction enables visualization of small vessels for optimization of trajectory planning. METHODS: A total of 25 patients underwent selective angiography before Stereo EEG planning. Syngo DynaCT"! (Siemens, Munich, Germany) was used to create angiographic CT (ACT). Arterial contrast bolus of 22 mL was delivered with automated power injector at 1 mL/s over 22 seconds with 0.2 seconds delay, and imaging acquired over 20 seconds of acquisition through 220° of rotation. Trajectory planning was performed with merged T1-weighted, gadolinium enhanced (T1-Gd) MRI and ACT on WayPoint Navigator"! planning software (FHC Inc., Bowdoin, Maine). RESULTS: Small-caliber vessels in both superficial and deep locations were routinely identified on ACT but not on T1-Gd MRI, resulting in alteration of planned trajectory. Skull thickness identified on ACT also altered trajectory entry points, particularly in thinned areas of squamous temporal bone and adjacent to prior craniotomies. CONCLUSION: Three-dimensional ACT improves the resolution of small-caliber vessels due to image acquisition throughout the late arterial to early venous phase. This is particularly important during the planning of complex Stereo EEG trajectories.